Avaliação da viscosidade e fluxo salivar em relação a condição periodontal e os níveis de compostos sulfurados voláteis - Maiza Luiza Vieira Silva (2014)
Although there are several reports in the literature on the composition of saliva, there are few studies investigating physical properties of saliva. The purpose of this study was to evaluate viscosity and salivary flow and in patients with periodontal disease and elucidate the association with the volatile sulfur compounds. Materials and Methods: A cross-sectional study in which 124 subjects were divided into periodontally healthy, gingivitis, slightmoderate periodontitis and advanced periodontitis, according to the periodontal parameters. Clinical salivary viscosity, viscosity laboratorial of stimulated saliva, by DV-III Brookfield rheometer, salivary flow rate and periodontal parameters of probing depth, clinical attachment level and bleeding on probing were evaluated. The concentrations of volatile sulfur compounds by gas chromatographic method, OralChromaTM (Abilit, Osaka), were mensured. Results: The results were statistically analyzed using SPSS version 17.0, at a confidence level of 95%. Clinical salivary viscosity was negatively correlated with periodontal parameters, except bleeding on probing. Hyposalivation was positily correlated with periodontal parameters, sulfhydride (H2S) and methylmercaptan (CH3SH). Higher concentrations of H2S were observed in advanced periodontitis and gingivitis groups. H2S and high concentrations of CH3SH were positively correlated with periodontal parameters. Conclusion: Physical properties of saliva, low viscosity and flow, are correlated with periodontal disease, as well as high concentrations of H2S and CH3SH. Support: FAPEMIG (APQ-01835-13).